1961
DOI: 10.1071/ar9610661
|View full text |Cite
|
Sign up to set email alerts
|

The development of rumen function in the lamb.

Abstract: A series of experiments is presented, describing the development of the rumen function in grazing lambs and the effects of' diet on the rumen development of artificially reared lambs. In grazing lambs the volume of the abomasum contents showed little change with age. The volume of the rumen contents increased with age, and the rate of' this increase was most marked from 3 weeks of age onwards. The volume of the rumen contents, relative to both the liveweight and the volume of the abomasum contents, was constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
40
0

Year Published

1967
1967
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 3 publications
10
40
0
Order By: Relevance
“…In addition, while the greatest effect of diet seems to be in week 12, effect of inoculation was largest at week 8. These results are consistent with ideas of Wardrop and Coombe (1961) and Abecia et al (2014a,c). Wardrop and Coombe (1961) reported that the post-birth functional and physical development process of the rumen of lambs has 3 stages: non-ruminant (0-3 weeks of age), transition (3-8 weeks of age), and adult (8 weeks of age), where the type of diet and the rumen microbial inoculation from adults would be the most important factors affecting this process.…”
Section: Effect Of Diet and Inoculation On Ruminal Bacterial Communitsupporting
confidence: 96%
See 1 more Smart Citation
“…In addition, while the greatest effect of diet seems to be in week 12, effect of inoculation was largest at week 8. These results are consistent with ideas of Wardrop and Coombe (1961) and Abecia et al (2014a,c). Wardrop and Coombe (1961) reported that the post-birth functional and physical development process of the rumen of lambs has 3 stages: non-ruminant (0-3 weeks of age), transition (3-8 weeks of age), and adult (8 weeks of age), where the type of diet and the rumen microbial inoculation from adults would be the most important factors affecting this process.…”
Section: Effect Of Diet and Inoculation On Ruminal Bacterial Communitsupporting
confidence: 96%
“…These results are consistent with ideas of Wardrop and Coombe (1961) and Abecia et al (2014a,c). Wardrop and Coombe (1961) reported that the post-birth functional and physical development process of the rumen of lambs has 3 stages: non-ruminant (0-3 weeks of age), transition (3-8 weeks of age), and adult (8 weeks of age), where the type of diet and the rumen microbial inoculation from adults would be the most important factors affecting this process. More recently, Abecia et al (2014a,c) studying microbial colonization successions in the rumen of goat kids, found that the greatest scope for altering the bacterial community is during the first 2 weeks of life of the kids because stabilization of the bacterial community was detected after day fourteen of life.…”
Section: Effect Of Diet and Inoculation On Ruminal Bacterial Communitsupporting
confidence: 96%
“…In relation to quantity, the effects at wk eight indicate that the addition of rumen fluid (from either source) in difference to water stimulates fermentation. Inoculation can affect the complexity of the microflora (Fonty et al, 1983), and rumen development (Bomba et al, 2005) during the transition phase of the lamb from pre-ruminant to ruminant (Wardrop and Coombe, 1961), and our evidence supports the hypothesis that the lambs inoculated with rumen fluid possessed a more developed ruminal fermentation by wk eight that led to differences relative to InW lambs.…”
Section: Effect Of Inoculation On Lambssupporting
confidence: 84%
“…They used curarized lambs (20-25 days old) anaesthetized with chloralose. Spontaneous reticular contractions, as would be expected, were absent, since reticulo-ruminal structure and 200 GASTRIC EFFERENT UNITS function in lambs of this age, according to Wardrop & Coombe (1961), would still have been in a very primitive stage of development. Reticular contractions-were evoked by distending the reticulum or stimulating the central end of a cut abomasal nerve.…”
Section: Discussionmentioning
confidence: 85%